Causality assessment, severity and preventability of adverse drug reactions due to first-line antitubercular agents - Gunjan Upadhyay; Apexa B Shukla; Darshan J Dave (Universitas Ahmad Dahlan, 2022)
TB (Tuberculosis) is a common infectious disease affecting humans since very long time. Multidrug therapy with its associated adverse drug reactions is one of the major concerns for the management of TB. The current study has been conducted for identifying causality assessment, severity as well as preventability of first-line anti-tubercular agents. All the diagnosed patients of tuberculosis attending TB and chest department of tertiary care hospital of western India and received Anti-TB drugs over 6 months enrolled in the study. Demographic details, suspected drugs/groups, causality assessment, severity assessment, and preventability assessment were analyzed from reported suspected ADR (adverse drug reaction) forms. Throughout the research period of 6 months, 500 patients received Anti-TB drugs. Among them, (10%) 50 patients developed 121 adverse drug reactions. According to the WHO causality scale, 66 (54.54%) ADRs were classified as ‘probable’ and 53 (43.8%) ADR were ‘possible’. More than half of the reactions (31, 62%) were mild on the severity scale while most of the ADRs were definitely (34, 68%) preventable as per the preventability scale. Gastrointestinal system is the most common affected system (54, 47.62%) followed by dermatological disorders (26, 23.01%) and Liver and biliary system (20, 16.52%). Isoniazid (46, 38%) and Rifampicin (40, 33%) were the common cause of first-line antitubercular agents for ADRs. ADRs to antitubercular agents are a major concern for patient compliance. Patient education, intensive reporting, and management can be helpful to improve the outcome of antitubercular therapy.